1972
DOI: 10.2134/agronj1972.00021962006400010011x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Conditions and the Coadministration of Growth Retardants on the Response of Sugarcane to Foliar Treatment with Gibberellin1

Abstract: Poor yields of sucrose from sugarcane are often associated with low sucrose:cane ratios, particularly when climatic conditions tend to favor stem elongation rather than sucrose accumulation. Plant growth regulators may be used to modify environmental effects on the growth of sugarcane and thus alter the balance between utilization and storage of sucrose. The objectives of this study were to investigate the influence of temperature, soil moisture, and the coadministration of plant growth retardants on the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Both variables show a strong inverse relationship with Brix, i.e., the lower the moisture index and the cooler the evenings, more favorable the conditions for ripening. Yates (1972) found that the low air temperatures promoted ripening more effectively than low soil moisture. These results were also reported by Glover (1971), who suggested that in places where there is no water defi ciency, the average air temperature needs to be lower than 21 °C for three months to begin the ripening process.…”
Section: Air Temperaturementioning
confidence: 98%
“…Both variables show a strong inverse relationship with Brix, i.e., the lower the moisture index and the cooler the evenings, more favorable the conditions for ripening. Yates (1972) found that the low air temperatures promoted ripening more effectively than low soil moisture. These results were also reported by Glover (1971), who suggested that in places where there is no water defi ciency, the average air temperature needs to be lower than 21 °C for three months to begin the ripening process.…”
Section: Air Temperaturementioning
confidence: 98%
“…Thus, there is a positive return between fixed and consumed carbon, resulting in a greater storage. For Yates (1972), the low air temperatures influence more the interruption of sugarcane growth than water stress. Nevertheless, according to Cardozo and Sentelhas (2013), there is no consensus on the thermal parameters of the crop and, in tropical areas, the low air temperatures may not be sufficient to affect the maturation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that increasing temperature decreases the responsiveness to application of an exogenous GA and that increasing temperature alone often simulates the effect of GA on intemode elongation (Junttila, 1970;Lester and Carter, 1970;Yates, 1972). These results suggest that at higher temperature, GA metabolism, or sensi tivity to GA, has been decreased compared with that at lower temperature.…”
Section: Review Of Literaturementioning
confidence: 97%